2014
DOI: 10.1590/s1982-56762014000500006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV-B radiation on Lecanicillium spp., biological control agents of the coffee leaf rust pathogen

Abstract: Coffee leaf rust is the main disease of coffee and its causal agent is naturally hyperparasited by Lecanicillium lecanii, indicating its potential for biocontrol. Ultraviolet-B (UV-B) radiation is an important factor that interferes on application of biocontrol agents, and Lecanicillium can be affected by UV-B. The objective of this work was to evaluate the effects of UV-B on Lecanicillium isolates and on its capacity to colonize rust lesions. There were variations among Lecanicillium strains in sensitivity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…C. rosea was applied at 10 7 conidia mL −1 (white circles) and at 10 6 conidia mL −1 (black circles). the other hand, Galvão and Bettiol (2014) observed the most tolerant strain of L. lecanii, found naturally hyperparasitising urediniospores of Hemileia vastatrix in coffee leaf rust lesions, had an LD 50 of 1.63 kJ m −2 for UV-B radiation exposure, and is therefore more sensitive than C. rosea. Our work corroborates the hypothesis raised by Ignoffo and Garcia (1992) that the colour of conidia is correlated with tolerance to solar radiation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…C. rosea was applied at 10 7 conidia mL −1 (white circles) and at 10 6 conidia mL −1 (black circles). the other hand, Galvão and Bettiol (2014) observed the most tolerant strain of L. lecanii, found naturally hyperparasitising urediniospores of Hemileia vastatrix in coffee leaf rust lesions, had an LD 50 of 1.63 kJ m −2 for UV-B radiation exposure, and is therefore more sensitive than C. rosea. Our work corroborates the hypothesis raised by Ignoffo and Garcia (1992) that the colour of conidia is correlated with tolerance to solar radiation.…”
Section: Discussionmentioning
confidence: 95%
“…Ultraviolet radiation inhibits the conidial germination of other beneficial organisms, such as Metarhizium, Lecanicillium and C. rosea on the phylloplane (Braga et al, 2001a;Costa et al, 2001Costa et al, , 2012Costa et al, , 2013Galvão & Bettiol, 2014). Competition is the most important mechanism of C. rosea to control B. cinerea in strawberry plants, and the applied concentration of the biocontrol agent conidia seems to have a crucial role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the fungal colonies are directly exposed to different UV-B radiation doses and the experiments are focused on the effect of UV-B radiation on growth, sporulation and propagules germination. The main micro-organisms used is these studies are the biological control agents, once the UV-B radiation is a factor that interfere in the efficacy of biological products Galvão and Bettiol, 2014;Rangel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that Lecanicillium isolates can be highly sensitive to various biological substances and non-synthetic factors. Galvão and Bettiol (2014) showed the high susceptibility of Lecanicillium genera to UV-B radiation, while Mehrparvar et al (2016) determined the antifungal activity of two essential oils at low concentrations for the growth of L. fungicola.…”
Section: M9mentioning
confidence: 99%